ETNOBOTANI TUMBUHAN OBAT OLEH MASYARAKAT DAYAK MERATUS DESA HARUYAN DAYAK KECAMATAN HANTAKAN KABUPATEN HULU SUNGAI TENGAH PROVINSI KALIMANTAN SELATAN - Iin Mariska; Trisnu Satriadi; Gusti Abdul Rahmat Thamrin (Universitas Lambung Mangkurat, 2021)
This study aims to identify medicinal plants by the Dayak community, and how to process and use them based on indicated symptoms or diseases. Haruyan village inhabited by indigenous Dayak Dayak Meratus are believed to have knowledge in the use of medicinal plants. Dayak community-owned greatness variety such as belief in ancestral spirits History and ethnobotany study they did in traditional medicine. This study used a descriptive method with in-depth interviews with selected informants, namely traditional leaders and traditional healers. A questionnaire was used to help focus the interview. The results obtained show that there are 30 species of medicinal plants used for disorders of supernatural beings, stomatch aches, broken bones or knots, toothaches, wounds, chills, ulcers, paralysis (stroke), and diarrhea. Leaves are the most widely used part of the plant at 63.3%. Processing of plant parts and their use as medicine can be done in 5 ways, respectively.Keywords: Ethnobotany; Medicinal Plant; Dayak Meratus; Haruyan Dayak Village